Oxygen Deprivation Modulates EGFR and PD-L1 in Squamous Cell Carcinomas of the Head and Neck - Zahnreich, Sebastian; Gebrekidan, Senayit; Multhoff, Gabriele; Vaupel, Peter; Schmidberger, Heinz; Mayer, Arnulf (Frontiers in Oncology, 2021)
Abundance and signaling of the epidermal growth factor receptor (EGFR) and programmed cell death protein ligand 1 (PD-L1) in head and neck squamous cell carcinoma (HNSCC) are not only genetically determined but are also subject to the traits of the tumor microenvironment, which has hitherto not been clarified completely. We investigated the impact of hypoxia on the EGFR system and on PD-L1 in six HPV negative HNSCC cell lines in vitro and in FaDu xenografts in vivo. Protein levels of EGFR, AKT, pAKT, ERK1/2, pERK1/2, CA IX, cleaved PARP (apoptosis), LC3B (autophagy), and PD-L1 were quantified by western blot after oxygen deprivation or CoCl2, staurosporine, and erlotinib treatment. In FaDu xenograft tumors the expression of EGFR, CA IX andCD34 staining were analyzed. Reduced oxygen supply strongly downregulated EGFR protein levels and signaling in FaDu cells in vitro and in vivo, and a transient downregulation of EGFR signaling was found in three other HNSCC cell lines. PD-L1 was affected by oxygen deprivation in only one HNSCC cell line showing increased protein amounts. The results of this study indicate a significant impact of the traits of the tumor microenvironment on crucial molecular targets of cancer therapies with high clinical relevance for therapy resistance and response in HNSCC.